PERAN GURU DALAM MENGATASI PERILAKU BULLYING PADA PESERTA DIDIK KELAS VI DI SD 1 WERGU WETAN - Sari, Diah Fatma; Azzahra, Wieline Dewi; Setiawaty, Rani (Universitas Muhammadiyah Tangerang, 2024)
Bullying is a social injustice that often occurs in schools. Bullying can also make students feel like criminals and troublemakers. Apart from that, bullying also has a negative impact, both for the victim and the perpetrator. If bullying like this occurs in SD/MI, then a teacher's behavior is needed so that the teacher is able to recognize, understand and help his students. The aim of this research is to understand the strategies teachers use to overcome bullying at school. This research methodology uses a qualitative research approach with an exploratory method. The analysis findings show that the teacher's response to bullying among students is to treat them as individuals which fosters a sense of belonging, provides them with guidance and support, and helps them overcome problems related to bullying so that they can reduce bullying that occurs in the school environment class.